The status of pediatric surgery in Malawi: a narrative mini-review - Flocks Monaghan, Celina; Pittalis, Chiara; Byrne, Elaine; Hussein, Israa; Chilunjika, Tiyamike; Nandi, Bip; Borgstein, Eric; Gajewski, Jakub (Frontiers in Pediatrics, 2023)
Introduction: Pediatric surgery is essential to a well-functioning health system. Unmet surgical needs contribute to 6.7% of pediatric deaths in Malawi. Understanding the current state of pediatric surgical care in Malawi is necessary to recognize gaps and opportunities in service delivery and to develop evidence-based national planning and solutions.Methods: This narrative mini review synthesized the literature on the state of pediatric surgery in Malawi through the pillars of the World Health Organization's Health System Building Blocks. A search of PubMed and Embase databases was executed to identify relevant studies and a thematic analysis was performed. Further, to ensure contextual accuracy, pediatric surgeons from Malawi were consulted and involved in this review.Results: Twenty-six papers were identified. In Malawi's central hospitals, there are six specialist pediatric surgeons for a pediatric population of more than eight million. There is limited pediatric surgical capacity at the district hospitals. There is little to no written evidence of the national governing and finance structures in place for pediatric surgical services.Discussion: In countries like Malawi where most of the population are children, national planning must prioritize improvement of services for this age group. This review highlights the current gaps in pediatric surgical services in Malawi that can inform national surgical planning.